Teachers' Efforts in Implementing Multicultural Education to Strengthen the Values of Honesty, Tolerance, and Peace in Early Childhood - Fidiah Ningrum; Ferdian Utama; Leli Fertiliana Dea (Bulletin of Early Childhood, 2025)
This study aims to describe teachers' efforts in implementing multicultural education to strengthen the values of honesty, tolerance, and peace in early childhood at RA Nurul Muttaqin. This study uses a qualitative descriptive approach with field research. Data were obtained through observation, interviews, and documentation with teachers, students, and parent representatives. The results show that the instillation of character values is carried out through consistent daily habits and integrated into learning activities. Teachers act as role models in displaying honest, tolerant, and peace-loving behavior, as well as creating a safe, inclusive, and conducive classroom environment. The value of honesty is formed through the habituation of responsibility and openness, tolerance is developed through group activities and social interactions, while peace-loving is instilled through persuasive conflict resolution and sociodrama activities. Play activities are the main medium for internalizing values because they provide enjoyable direct experiences for children. In addition, multicultural education strategies implemented through the introduction of cultural diversity and collaborative activities can foster mutual respect and strengthen a sense of togetherness. The research findings confirm that the success of early childhood character formation is greatly influenced by the consistency of habits, teacher role models, and an inclusive and harmonious learning environment. Thus, the application of multicultural education contextually is an effective approach in shaping children's social character from an early age.